2003
DOI: 10.1124/jpet.102.046979
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/Orphanin FQ and Its Receptor—Potential Targets for Pain Therapy?

Abstract: The neuropeptide nociceptin, also called orphanin FQ (N/OFQ), is the endogenous agonist of the N/OFQ peptide receptor (NOP receptor). Both N/OFQ and the NOP receptor share a high degree of homology with classical opioid peptides and opioid receptors, respectively, and use similar signal transduction pathways as classical opioids. The NOP receptor has thus been regarded as the fourth member of the opioid receptor family. Despite this close relationship, 7 years of research have demonstrated that the N/OFQ syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 56 publications
4
57
0
3
Order By: Relevance
“…Spinal morphine produced a dose dependent and robust antinociceptive effect in line with previous findings (Kosson et al, 2008). A similar antinociceptive action has been promoted by the spinal injection of N/OFQ accordingly to (Schroder et al, 2014;Zeilhofer and Calò, 2003;). Compared to morphine, N/OFQ displayed similar potency but reduced maximal effects.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Spinal morphine produced a dose dependent and robust antinociceptive effect in line with previous findings (Kosson et al, 2008). A similar antinociceptive action has been promoted by the spinal injection of N/OFQ accordingly to (Schroder et al, 2014;Zeilhofer and Calò, 2003;). Compared to morphine, N/OFQ displayed similar potency but reduced maximal effects.…”
Section: Discussionsupporting
confidence: 77%
“…NOP( þ/þ ) and NOP( À / À) rats displayed similar pain threshold in the Paw pressure test. This is in line with studies performed in NOP knockout mice (Depner et al, 2003;Nishi et al, 1997) suggesting that the endogenous N/OFQ -NOP receptor system does not tonically control nociceptive transmission (Zeilhofer and Calò, 2003). The spinal injection of morphine in NOP( À / À ) rats produced a clear antinociceptive effect while N/OFQ, UFP-112 and UFP-113 were completely inactive.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These pharmacological features are highly desirable especially for investigating those conditions and states in which a selective and prolonged stimulation of NOP receptor is beneficial, including anxiety states [21,28], drug addiction [15,48], anorectic conditions [16], spinal analgesia (as indicated by laboratory animals [54] as well as primate [35] studies), cough and possibly other respiratory diseases [40], acute heart failure [26,34], and, as indicated by clinical studies, urinary incontinence due to overactive bladder [37][38][39]. Peak changes in mean arterial pressure and heart rate produced immediately following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…30,39 It has been suggested that intrathecal N/OFQ-induced hyperalgesia may be mediated by tachykinin NK1 receptors in the mouse spinal cord. 39,40 Although intrathecal N/OFQ did not produce hyperalgesic effects like intrathecal substance P in monkeys, more studies are warranted to elucidate the relationship of intrathecal substance P with other neurotransmitter systems in the modulation of nociceptive processing of the primate spinal cord.In contrast, intrathecal administration of DAMGO 10 nmol significantly produced antinociceptive effects, manifested as elevated tail-withdrawal latencies in 50 C water. These effects are consistent with rodent studies, indicating that intrathecal DAMGO is a potent m-opioid antinociceptive agent.…”
mentioning
confidence: 99%